A rapid assessment of mortality surveillance in Uganda. - Marie Gorreti Zalwango; Caroline Kyozira; Mariam Nambuya; Martin Bulamu; Allan Muruta (PLOS Global Public Health)
Mortality surveillance aids in identifying and addressing causes of death allowing health systems to adapt and respond effectively. An assessment of mortality surveillance in Uganda was conducted from November 2023 to June 2024 through data reviews and plenary discussions engaging various stakeholders in Uganda. Eight (8) workshops/meetings were conducted over a period of eight months to generate information on mortality data sources, processes of data generation and challenges affecting the system. Responses from the meetings and workshops were recorded and transcribed. Data were thematically analysed and presented as descriptive narratives. Quantitative data from district health information system version. 2 (DHIS2) was analyzed using excel and presented using charts and tables. The rapid assessment of mortality surveillance in Uganda highlighted opportunities for improved mortality surveillance through the existence of various sources of data. It was highlighted that 66.9% of the death occur in communities, however, there is a major data completeness gaps where suboptimal data from the community is feed into the national health statistics database (DHIS2) to enable stakeholder analysis and utilization. Furthermore, a number of data quality issues were identified in the health facility generated data where 33% of the deaths occur. These include: data completeness where the national referral specialized health institutes do not feed their data into the national data base, late reporting and the lack of coordination and standardisation of reporting among the various partners. The existence of structures to conduct mortality surveillance in Uganda presents an opportunity for improved mortality surveillance despite the highlighted gaps and challenges. Adoption of strategies aimed to enable the successful implementation of an efficient mortality surveillance program like: strengthening governance and operations of death reporting activities, establishing a clear definition of institutional roles and responsibilities, raising awareness and advocacy at all levels, building technical capacities, improving allocation of resources, and leveraging on shared interests by both implementing and development partners could improve mortality surveillance and the health of the population through utilisation of the generated data.